Integrating Ambulatory Care Pharmacists Into Value-Based Primary Care: A Scalable Solution to Chronic Disease - Alexander J. Blood; Harry Saag; Adam Chesler; Dalia Ameripour; Max Gutierrez; Van Nguyen; Cassandra Richardson; Clive Fields; Jen Clair; Aaron Yao; Sashi Moodley (Journal of Primary Care & Community Health)
Introduction/Objectives: Patients living with chronic diseases require more medical attention, including more visits to primary care. However, primary care providers are overburdened, and this specialty is attracting fewer new providers than before. Clinical pharmacists can augment these efforts by improving disease state control. In this cohort study, we aimed to demonstrate a retail pharmacy hired and trained clinical pharmacist within a value-based primary care clinic network can improve hypertension (HTN) and type 2 diabetes mellitus (T2DM) control. Methods: In this cohort study, a pharmacist, enabled by a collaborative drug therapy management agreement, prescribed and titrated therapies for HTN and T2DM. Primary outcomes were pre- to post-index changes in hemoglobinA1c, systolic, and diastolic blood pressure (BP) measures. Results: The HTN cohort consisted of 43 patients and the T2DM cohort consisted of 125 patients. The difference-in-differences (β) in the HTN group was −10.2 mmHg ( P  < .01) for systolic BP and −2.0 mmHg ( P  = .42) for diastolic BP. The β in the T2DM group was −1.16% ( P  < .001). Conclusions: Statistically significant reductions in systolic BP and hemoglobinA1c were observed in the pharmacist-managed group compared with matched controls. These results demonstrate that pharmacist integration into a value based primary care clinic may improve measures of chronic disease associated with morbidity and mortality.